Gambaran Faktor Risiko Status Gizi dan Riwayat Kejang Keluarga pada Anak Kejang Demam di RS Al Islam Bandung periode 2021–2022 - Andika Ilham Rahmadi Prianza; Herry Garna; Buti Azfiani Azhali (Bandung Conference Series: Medical Science, 2024)
Abstract. Febrile seizures are seizures in children aged 6-60 months (peak 12–18 months) and are triggered by a body temperature of 38°C (100.4°F) or higher, which is not the result of CNS infection or metabolic imbalance, and occurs without a previous history of febrile seizures. Febrile seizures have various risk factors, one of which can be seen from nutritional status and family history of seizures. This study aims to determine the risk factors for nutritional status and family history of seizures in children with febrile seizures at Al Islam Hospital Bandung for the 2021-2022 period. Researchers used descriptive methods with total sampling techniques in sampling and calculated the frequency distribution. The population selected in this study were inpatients/outpatients/polyclinics/ICU pediatric patients aged 6 months-5 years who were diagnosed with febrile seizures based on medical record data. With the sampling technique, namely total sampling, the number of research samples obtained was 184 children. The results of this study are: (1) The nutritional status of children with febrile seizures mostly had normal nutritional status (-2 to 2) as much as 52.2%, underweight nutritional status (-3 to <-2) as much as 24.5%, very underweight nutritional status (<-3) as much as 22.3%, and obese nutritional status (>2) as much as 1.0%; (2) Most children with febrile seizures did not have a family history of seizures compared to having a family history of seizures (77.7% versus 22.3%). Abstrak. Kejang demam adalah kejang pada anak usia 6–60 bulan (puncaknya 12–18 bulan) dan dicetus oleh suhu badan 38°C (100,4 ° F) atau lebih tinggi, yang bukan merupakan hasil infeksi SSP atau ketidakseimbangan metabolisme, dan terjadi tanpa adanya riwayat kejang demam sebelumnya. Kejang demam memiliki faktor risiko yang bervariasi salah satunya dapat dilihat dari status gizi dan riwayat kejang keluarga. Penelitian ini bertujuan untuk mengetahui gambaran faktor risiko status gizi dan riwayat kejang keluarga pada anak kejang demam di RS Al Islam Bandung periode 2021–2022. Peneliti menggunakan metode deskriptif dengan teknik total sampling dalam pengambilan sampel dan dihitung distribusi frekuensinya. Populasi yang dipilih dalam penelitian ini adalah pasien anak rawat inap/jalan/poliklinik/IGD usia 6 bulan–5 tahun yang didiagnosis kejang demam berdasarkan data rekam medik. Dengan teknik pengambilan sampel yaitu total sampling diperoleh jumlah sampel penelitian sebanyak 184 anak. Hasil dari penelitian ini adalah: (1) Status gizi anak kejang demam sebagian besar memiliki status gizi normal (-2 s.d. 2) sebanyak 52,2%, status gizi kurus (-3 s.d. <-2) sebanyak 24,5%, status gizi sangat kurus (<-3) sebanyak 22,3%, dan status gizi gemuk (>2) sebanyak 1,0%; (2) Sebagian besar anak kejang demam tidak mempunyai riwayat kejang keluarga dibanding dengan mempunyai riwayat kejang dalam keluarga (77,7% versus 22,3%).